Pre-Plant Nitrogen Rate and Application Method and Side-Dress Nitrogen Rate Effects on No-Till Corn Grown on a Claypan Soil - D. W. Sweeney; D. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2020)
Average corn yield in 2019 was increased by 14 bu/a with knife application of pre-plant nitrogen (N) fertilizer compared with broadcast application. Applying N more than doubled yield of corn grown without N. In general, applying side-dress N increased yields compared to yields obtained with only pre-plant applications.
Keywords: nitrogen; rate; application method; side-dress; corn; no-till